Efektivitas Penangganan Gizi Kurang Pada Balita Melalui Pos Gizi Di Wilayah Kerja Puskesmas Botania - Andolina, Nuari; Fitriani; Eka Fitri Amir; Feny Puput Indrawati (Akademi Kebidanan Bunga Husada Samarinda, 2025)
Good nutrition is very important for the growth of infants and toddlers because it can affect the formation of organs and their functions, as well as nerve function, and the immune system. Poor feeding will cause nutritional disorders in infants such as obesity, malnutrition, severe malnutrition, and stunting. Malnutrition is a state of lack of nutrients which includes short and thin elements, where body weight according to age (BB/A) is at -3 SD to <-2 SD from the WHO-NCHS growth standard (PMK, No. 2 of 2020). This study is an experimental study with a post-test only control group design where there are 2 (two) groups, namely the control group and one treatment group (experiment). The research was carried out in July - November at the Botania Health Center in 2024. The population and sample of this study were malnourished toddlers. Data analysis used univariate, bivariate analysis, and One Way Anova statistics. Based on the results of the experimental study on the group that participated in the Nutrition Post with a Pvalue of 0.001, which means there is a difference in the weight of toddlers, while in the group that did not participate in the Nutrition Post with a Pvalue of 0.065, which means there is no difference in weight. Based on the results of the study, it can be concluded that for the Nutrition Post activities at the Botania Health Center, only 1 has implemented the Nutrition Post, and for the Health Center that implemented the Nutrition Post, there was an increase in the weight of toddlers with malnutrition. For the planning, implementation and follow-up plan for the Nutrition Post activities, it has been going well even though there are still obstacles. It is hoped that the Nutrition Post activities can be implemented in all existing Posyandu so that the handling of malnutrition can be resolved quickly.